(untitled) (Archives of Criminology, 2008)
The aim of the article is to acquaint the reader with the problem of female delinquency by looking at the criminological theories crucial to the phenomenon. The text by Dagmara Woźniakowska-Fajst draws attention to the limitations of research approaches used in studies on female crime. The author argues that the theories used in criminology to study female offenders ignore gender differences and are based on the same factors that define male criminality. As women’s crime is considered a marginal occurrence, researchers try to explore it by looking for either unusual abnormalities or reasons why women are less likely than men to commit criminal acts. The material presented in the article comprises criminological theories that have been or are being used to study female criminality. The author lists those theories that identify the causes of female delinquency as the parenting style for girls, such as the theorythat criminal behaviour is learned(Sutherland), according to which women – whose primary group was to be a strongly controlling family – were less likely to learn criminal behaviour than boys. Differential association theories claim that women’s criminal behaviour is strongly related to their aberrant lifestyles. These women observe criminal and antisocial behaviour in their mothers, fathers, cousins, and siblings over many years and internalise this way of being as appropriate. Next, the author cites biochemical theories that attempt to explain women’s criminal behaviour as a result of hormonal and biological changes caused, for example, by premenstrual syndrome (PMS) or pregnancy. Then, the text presents theories related to the position of women in society, such as Merton’s strain theory of deviance, Cohen’s theory of cultural syndromes, or Cloward and Ohlin’s theory of differential opportunity systems. In this case, the means do not have to be specific tools. It is sufficient that the set of values or attitudes that facilitate the unlawful behaviour are accepted among women. This theory is easier to ‘fit’ into criminal acts committed by women. Further on, Woźniakowska-Fajst mentions Tannenbaum’s social labelling theory, according to which deviants (in this case women) are labelled criminals based on the stereotypical perception of them. The articlealso presents the main tenets of control theories, including the social bond theory by Hirschi and Hinderlang and the power-control theory by Hagan, which, although used primarily to study male delinquency, sought to explain the lower rates of delinquency among girls by drawing attention to the impact of parents’ careers and social class on the prevalence of criminal acts among minors. Finally, the article discusses integrated theories, which are investigations that try to obtain a single model from a combination of known criminological theories. The author believes that these theories are the future of criminological research on women’s crime and stresses the positive influence of the contemporary trend in modern criminology, which is marked by a broader view of the causes of criminal behaviour.